2016
DOI: 10.1097/bot.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pelvic Binder Placement on OTA Classification of Pelvic Ring Injuries Using Computed Tomography. Does It Mask the Injury?

Abstract: Diagnostic level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…Bonner et al [ 41 ] have shown that correctly placed pelvic binders could effectively reduce unstable pelvic ring injuries. This is supported by a recently published study by Swartz et al [ 42 ], who have shown that pelvic binders could mask the true nature of the fracture pattern and in particular made Tile C and B3 fractures look like B2 fractures. Since in the present series about half of the fractures were classified based on imaging with pelvic binders in place, it can be hypothesized that some B1 fractures may have been classified as B2 fractures.…”
Section: Discussionsupporting
confidence: 56%
“…Bonner et al [ 41 ] have shown that correctly placed pelvic binders could effectively reduce unstable pelvic ring injuries. This is supported by a recently published study by Swartz et al [ 42 ], who have shown that pelvic binders could mask the true nature of the fracture pattern and in particular made Tile C and B3 fractures look like B2 fractures. Since in the present series about half of the fractures were classified based on imaging with pelvic binders in place, it can be hypothesized that some B1 fractures may have been classified as B2 fractures.…”
Section: Discussionsupporting
confidence: 56%
“…There are complications associated with their use, such as pressure sores, tissue necrosis and nerve palsy,7 especially if they are left on for a prolonged period of time. Pelvic binders may mask the “severity” of the pelvic injury on CTs, particularly APC patterns 17. It is rare to completely hide any injury, but it does happen 17,18.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic binders may mask the “severity” of the pelvic injury on CTs, particularly APC patterns 17. It is rare to completely hide any injury, but it does happen 17,18. This is not a reason to avoid PCCD usage but an example of how efficient they are at accomplishing their goal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations